The tax-price elasticity of offshore tax avoidance: Evidence from Ecuadorian transaction data - Jakob Brounstein (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study leverages a unique data set on the universe of transactions exiting the Ecuadorian economy to estimate the tax-price elasticity of demand for tax-sheltering activities using offshore fiscal havens. I determine this elasticity quasi-experimentally by comparing the evolution in funds sent by individuals and corporations to tax havens for different purposes (e.g. dividend payments, bank account deposits) versus similar transactions with non-tax havens around changes to the Ecuadorian Impuesto a la Salida de Divisas, which effectuated an ad valorem tax on transfers to tax havens. I document large responses of funds sent abroad for tax-avoidance and tax-evasive purposes to the tax price of transacting with fiscal havens. I also provide evidence that individuals with financial connections to tax havens declare additional capital income on their tax returns in the post-period, and due to the progressivity of the tax schedule pay a higher average income tax rate as a result.
Keywords: F38; H23; H26; H30; 330; tax evasion; tax avoidance; tax havens